Acute Decompensated Heart Failure+Atrial Fibrilation : Case Report - Ade Giriayu Anjani; Shofyatul Fajriyah (Sean Institute, 2024)
Heart Failure is a health issue with high mortality and morbidity rates in both developed and developing countries, such as Indonesia. The prevalence of heart failure in Asia is generally similar to that reported in Europe (1–3%), while in Indonesia, the prevalence is reported to be greater than 5%. Heart failure increases among geriatric patients, affecting 6% of those aged 60-79 years and up to 14% of those over 80 years old. Acute Decompensated Heart Failure (ADHF) is the progressive worsening of symptoms and clinical signs of heart failure in patients who have been previously diagnosed with the condition. The underlying mechanisms of clinical deterioration in patients include increased congestion and disease progression. ADHF and AF often occur together and can lead to hemodynamic instability and death. AF is the most common supraventricular dysrhythmia in patients with ADHF, with a prevalence of 25%-40%. The combination of ADHF and AF results in adverse clinical outcomes, including prolonged hospitalization and increased mortality. A 50-year- old woman complained of shortness of breath accompanied by palpitations that started 10 days before hospital admission and worsened in the last 2 days. The patient has a history of an enlarged heart for the past 3 years. A transthoracic echocardiogram revealed atrial fibrillation with a rapid ventricular rate (RV) of 90-130 beats per minute, left ventricular dilation (LVIDd 5.5 cm), decreased right ventricular systolic function (TAPSE 1.4 cm), left atrial dilation (LAVI 64.45 ml/m2), and right atrial dilation (RA major 5.8 cm). The electrocardiogram showed atrial fibrillation, abnormal ST & T waves, and prolonged ǪT interval.